Análisis Financiero a la empresa “Socool” en la ciudad de Quito, periodo: 2011 - 2012 - Chanatasig, Aurelio (2014)
The present work of investigation “Analysis Financial to the Enterprise “SOCOOL” in the City of Quito, Period: 2011 – 2012”, realize in the Enterprise “SOCOOL”, have many years to dedicate in the area of sale pawn of to dress trying to attend at all clients, delivering efficiency in the service and the quality of pawn of to put on, to have such as give compliment to one of the requirement previous to obtain the degree the Engineer in Accounting and Advocate. Giving compliment to the objectives to establishes is practical the Analysis Financier to the Financial States intervening the Analysis Vertical, Horizontal and the application of Indicate Financiers with the finality of determine the problems of variations, like also the degree of liquidates, indebted, activity, and rental of the enterprise, to optimize the process of actions in the administration of the entity, of such manner what may be to take the decisions more adequate intervening the establishment of standards and procedures of Analysis to the Financier States. With the results of Analysis each demonstrate that have exist greater action Financier and to manage in form adequate the Import of the merchandises to deliver to whole the clients in form opportune and efficient. For it that to recommend to maintain the application of Analysis to the Financier States, of conformity with the behavior of the projections, with the purpose that the management to apply, one occasion on the year, with the purpose of take decisions adequate.